ABOUT QUEEN BIBIKHANOM OF TEMUR (KONFERENSIYA, 2026)
The article also discusses the reign of the Timurids, who liberated our homeland from the Mongols, united it, made a great contribution to world civilization, and created a unique second Renaissance. One of them is Takina Hatun, the mother of Amir Temur, one of the respected ladies of the land of Kesh, and the other is Sahibkiran Amir Temur's close associate, his faithful wife Saraymulkkhanim (Bibikhanim). This article also attempts to provide information about the owner of high intelligence or the Timurid princess Bibikhanim, based on certain sources.